Juvenile Detention and Correctional Facility Census, 1984-1985 ([Verlag nicht ermittelbar], 1987)
This survey is the eighth in a series of data collection efforts aimed at providing information on the number and type of juveniles placed in state and local residential facilities for juvenile offenders. Six types of public and private facilities are covered: (1) detention centers, (2) shelters, (3) reception or diagnostic centers, (4) training schools, (5) ranches, forestry camps, and farms, and (6) halfway houses and group homes. Survey items include facility capacity, number of full-time and part-time staff, number of admissions and discharges, average quarterly population, and expenditures by the facility. Data for facility residents include age, sex, and average length of stay.